Lineární rovnice s jednou neznámou

1)        Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad 4a-5=3\left( 3-a \right)

\displaystyle b)\quad 2=2\left( 5c+1 \right)

\displaystyle c)\quad c+7=-3\left( c+11 \right)

\displaystyle d)\quad 3x-4=4-\left( -5x+6 \right)

\displaystyle e)\quad 4\left( d-5 \right)-7=13-d

\displaystyle f)\quad 5-5\left( x+4 \right)=2\left( x+3 \right)

\displaystyle g)\quad 6\left( 2-y \right)+3y=12-3y

\displaystyle h)\quad a-7\left( 2a-7 \right)=9-5a

\displaystyle i)\quad 2\left( x+6 \right)-\left( 5-4x \right)=6x

\displaystyle j)\quad 3b+5\left( 2b+9 \right)-19=0

 

2)        Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad a+7-3\left( 2a+5 \right)=-2\left( a-15 \right)-5

\displaystyle b)\quad 5\left( 3m-2 \right)-9\left( 5-2m \right)=4m+2\left( 5m+1 \right)

\displaystyle c)\quad 2=10-3\left( x+7 \right)+5\left( 1-x \right)+6x

\displaystyle d)\quad 2-6\left( 1-x \right)+x=4\left( 2x-1 \right)-x

\displaystyle e)\quad 3y+4\left( 7-2y \right)-6\left( y+14 \right)=-1-\left( y+5 \right)

\displaystyle f)\quad x-6\left( 13-2x \right)-2=2\left( x-3 \right)-10-5x

\displaystyle g)\quad 10\left( 5a-4 \right)+3\left( 2a-1 \right)=12a-\left( 2-3a \right)

\displaystyle h)\quad 5\left( n+9 \right)-\left( -2n-11 \right)+8=3n+16

\displaystyle i)\quad 7\left( 3b+4 \right)-4\left( b-5 \right)-2\left( 2b+11 \right)=0

\displaystyle j)\quad 2y-\left( 3-4y \right)+5=4\left( 2y+3 \right)-9

 

3)        Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{u}{5}-1=7-\frac{u}{3}

\displaystyle b)\quad 2+\frac{z}{4}=4+\frac{z}{2}

\displaystyle c)\quad \frac{x}{6}-5=1-\frac{x}{2}

\displaystyle d)\quad \frac{b}{5}-4=\frac{b}{2}+5

\displaystyle e)\quad \frac{1}{2}-\frac{n}{4}=-\frac{1}{2}-\frac{n}{3}

\displaystyle f)\quad \frac{v}{9}-\frac{4}{3}=\frac{v}{6}-\frac{1}{3}

\displaystyle g)\quad \frac{a}{2}-\frac{3}{8}=\frac{1}{4}-\frac{a}{8}

\displaystyle h)\quad \frac{x}{14}+\frac{3}{2}=\frac{x}{7}+\frac{9}{7}

\displaystyle i)\quad 2-\frac{2}{3}d=\frac{5}{6}-\frac{5}{4}d

\displaystyle j)\quad \frac{3}{5}r-3=-\frac{1}{5}-\frac{r}{10}

\displaystyle k)\quad \frac{11}{6}+\frac{2}{5}c=\frac{c}{3}+\frac{3}{2}

\displaystyle l)\quad 2x+\frac{7}{6}=\frac{x}{6}-\frac{2}{3}

\displaystyle m)\quad m+\frac{4}{7}=\frac{5}{3}m+\frac{4}{21}

\displaystyle n)\quad 1+\frac{4}{5}s=\frac{1}{40}-\frac{s}{2}

 

4)        Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad s-\frac{1}{6}\left( 3s+9 \right)-1=\frac{1}{2}\left( s-5 \right)

\displaystyle b)\quad x=\frac{2}{5}\left( 2x-7 \right)+\frac{x}{3}+2

\displaystyle c)\quad 1-\frac{3}{4}\left( 5-k \right)-\frac{1}{6}\left( k+9 \right)=4k+6

\displaystyle d)\quad n-\frac{2}{3}\left( 11-n \right)=\frac{1}{2}\left( 3n+1 \right)-7

\displaystyle e)\quad \frac{2}{3}\left( 7t-1 \right)-\frac{1}{4}\left( 3t+5 \right)-2t=0

\displaystyle f)\quad \frac{3}{4}-\frac{1}{2}\left( 7-4x \right)-x=\frac{1}{3}\left( 3x+8 \right)-12

\displaystyle g)\quad \frac{1}{2}\left( 5-3x \right)-\frac{4}{7}\left( 4x+11 \right)=2x+2

\displaystyle h)\quad \frac{5}{6}\left( 5a-6 \right)-1=2a+\frac{3}{4}\left( a-8 \right)

\displaystyle i)\quad 2v-6\left( 2v+3 \right)=\frac{1}{2}\left( 8-v \right)-\frac{3}{4}\left( v+6 \right)

\displaystyle j)\quad \frac{1}{3}\left( 7p-2 \right)=p-\frac{1}{6}\left( 5p+6 \right)+2\left( p+2 \right)

 

5)        Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{b-4}{3}=\frac{9-b}{2}

\displaystyle b)\quad \frac{3c+14}{4}=2

\displaystyle c)\quad x+2=\frac{6x+7}{5}

\displaystyle d)\quad \frac{16-5t}{7}=\frac{t+7}{2}

\displaystyle e)\quad \frac{2k+11}{4}=\frac{3}{4}

\displaystyle f)\quad \frac{7m+3}{10}=\frac{4-m}{5}

\displaystyle g)\quad \frac{z+7}{3}=1-\frac{3z+17}{6}

\displaystyle h)\quad r-\frac{3r-10}{8}=\frac{2r+7}{4}

 

6)        Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{3x-10}{3}-\frac{x}{2}-\frac{2x-13}{6}=0

\displaystyle b)\quad \frac{6-t}{4}-3=\frac{2t+6}{7}-\frac{t+4}{2}

\displaystyle c)\quad 1-\frac{7c-4}{9}-\frac{5-3c}{6}=\frac{c}{3}

\displaystyle d)\quad \frac{4z-6}{5}-\frac{3z-8}{4}=\frac{z-4}{20}+1

\displaystyle e)\quad \frac{1-3t}{2}+\frac{3t+11}{8}=1-\frac{5t-3}{4}

\displaystyle f)\quad \frac{2-x}{3}-\frac{x+8}{8}+\frac{5x+2}{6}=\frac{3x-4}{4}-2

 

7)        Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{3-2a}{4}+\frac{a+9}{3}-\frac{2a+10}{2}-\frac{1-5a}{4}=-1

\displaystyle b)\quad \frac{7v+6}{5}+\frac{2-5v}{2}=2+\frac{11v-4}{6}-\frac{8v-1}{3}

\displaystyle c)\quad k-\frac{2k-9}{3}-5=\frac{k-7}{2}-\frac{2k-19}{9}

\displaystyle d)\quad \frac{2}{3}m-\frac{5m+8}{4}-2=\frac{6-3m}{8}-\frac{m+20}{4}

\displaystyle e)\quad y-\frac{5y-6}{7}-\frac{2-7y}{4}=\frac{2y+1}{2}-\frac{1}{7}

\displaystyle f)\quad \frac{1-2x}{4}-2+\frac{2x+9}{5}=\frac{3x+10}{2}-\frac{3}{20}

\displaystyle g)\quad \frac{6-4s}{3}+\frac{8s+3}{6}-\frac{6s-5}{9}=1-\frac{4s+9}{6}

\displaystyle h)\quad \frac{5t-4}{6}-2=\frac{4-2t}{3}+\frac{3t-8}{2}

 

8)        Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{x-2}{3}=\frac{x+4}{7}

\displaystyle b)\quad \frac{x-2}{9}=\frac{x+3}{4}

\displaystyle c)\quad \frac{y+3}{4}-\frac{y-5}{3}=2

\displaystyle d)\quad \frac{y-4}{8}-\frac{y+5}{10}=-1

\displaystyle e)\quad \frac{3z+7}{3}-\frac{5+2z}{2}=1

\displaystyle f)\quad \frac{6z+7,5}{3}-\frac{2+8z}{4}=2

 

9)        Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad \frac{5x-3}{2}-\frac{1-7x}{3}=4x-1

\displaystyle b)\quad \frac{3x+7}{5}-\frac{8-x}{3}=x-1

\displaystyle c)\quad \frac{8x-1}{5}-\frac{3-2x}{4}=2x-1

\displaystyle d)\quad \frac{3x-8}{6}-\frac{6-3x}{5}=x-\frac{5}{2}

\displaystyle e)\quad \frac{2-5x}{2}-\frac{3-7x}{5}=1-\frac{x+6}{10}

\displaystyle f)\quad \frac{6+7x}{3}-\frac{5x-3}{6}=2-\frac{x+3}{2}

\displaystyle g)\quad \frac{2x-5}{6}+\frac{x+3}{4}=\frac{3-x}{3}-\frac{6-7x}{8}

\displaystyle h)\quad \frac{1-3x}{2}+\frac{2x-3}{4}=\frac{5-x}{6}-\frac{4x-8}{3}

 

10)        Řešte v \displaystyle \mathbb{R} rovnice a proveďte zkoušky:

\displaystyle a)\quad 3,6\left( 1-2x \right)-2,2x=2\left( 1,8-4,7x \right)

\displaystyle b)\quad 2,5\left( 2-3x \right)+6,3x=3\left( 1,2-0,6x \right)+1,1

\displaystyle c)\quad 2,8\left( 3-2x \right)+3,2x=6,3-2\left( x-1,4 \right)

\displaystyle d)\quad 3,1\left( 2-4x \right)+8,4x=-1,8-2\left( x-2,5 \right)